Impact Properties of Composite Materials: The Significance of Glass Microspheres - Sultan Ullah; Arvydas Palevicius; Giedrius Janusas; Zeeshan Ul Hasan (Tekstilec, 2025)
Due to their exceptional qualities, polymer matrix composite materials are finding more and more use in high-tech applications. The purpose of this work was to improve these composites' resilience to impact by adding glass microspheres to thermosetting phenolic resins. Glass fabric was used as the reinforcing material. The main objective of the study was to determine how different glass microsphere percentages affected the composites' mechanical characteristics. A fibre volume fraction of 0.6 was attained by utilising compression moulding to create the composites, which were made from four glass fabric plies. The mechanical properties were considerably improved by the addition of glass microspheres; the best results were noted at concentrations of 6–8%. More specifically, there was a noticeable improvement in tensile strength and a 6% rise in tensile modulus. Based on the results, the addition of glass microspheres to composite materials improves both their mechanical and energy-absorbing capabilities, thus making them more appropriate for use in impact applications.